Creative design software: Challenges and opportunities to the graphic designer in Zimbabwe - Chipambwa, Walter; Chimanga, Takunda (Journal of Graphic Engineering and Design, 2018)
The study sought to investigate the nature of issues facing the graphic designers with regards to software usage and upgrades. Technology has changed the way graphic designers do their job and this has brought some challenges and opportunities to the creative design industry in Zimbabwe. In depth interviews were carried with graphic designers currently in practice and also an open ended questionnaire was used to solicit for views from the designer perspective. From the findings it was concluded that younger designers are enrolling for the graphic design qualification in institutions of higher learning across the country. Most designers highlighted that they prefer using Adobe suite as a software package of choice even though they do not acquire the official proprietary software license. To a larger extent the graphic designers make a choice on software to buy depending with their hardware capabilities.